Postfledging habitat selection of juvenile middle spotted woodpeckers: a multi-scale approach - Ciudad, Carlos; Robles, Hugo; Matthysen, Erik (Ecography, 2009)
Despite its relevance for the persistence of populations, the ecological mechanisms underlying habitat use decisions of juvenile birds are poorly understood. We examined postfledging habitat selection of radio-tracked juvenile middle spotted woodpeckers Dendrocopos medius at multiple hierarchically-nested spatial scales in NW Spain. At the landscape and home range scales, old oak forest was the most used and selected habitat, young oak forests and pine plantations were avoided, and riverside forests were used as available. At a lower scale, birds selected larger diameter trees for foraging. Home ranges had higher densities of large deciduous trees (mainly oaks Quercus spp., but also poplars Populus spp. and willows Salix spp. 22 cm and 33 cm DBH) selected for foraging by juveniles than non-used areas. These results suggest that foraging conditions may drive, at least partly, habitat use decisions by juvenile birds. We also discuss the potential influence of intraspecific competition, the search for a future breeding territory in the early postfledging period and predation avoidance on habitat use decisions by juvenile birds. Contrary to previous studies on migrant forest birds, postfledging juvenile woodpeckers selected the same habitat as for the breeding adults (i.e. old oak forest), indicating that migrant and resident specialist avian species may require different conservation actions. Conservation strategies of woodpecker populations should consider the protection of old oak forests with high densities of large trees to provide suitable habitat to breeding adults and postfledging juveniles. The habitat improvement for this indicator and umbrella species would also favour other organisms that depend on characteristics of old-growth oak forests.
Keywords: foraging habitat use; habitat selection; juvenile birds; oak forests; postfledging (voyant)

Postfledging habitat selection of juvenile middle spotted woodpeckers: a multi-scale approach (Ecography, 2009)
Despite its relevance for the persistence of populations, the ecological mechanisms underlying habitat use decisions of juvenile birds are poorly understood. We examined postfledging habitat selection of radio-tracked juvenile middle spotted woodpeckers Dendrocopos medius at multiple hierarchically-nested spatial scales in NW Spain. At the landscape and home range scales, old oak forest was the most used and selected habitat, young oak forests and pine plantations were avoided, and riverside forests were used as available. At a lower scale, birds selected larger diameter trees for foraging. Home ranges had higher densities of large deciduous trees (mainly oaks Quercus spp., but also poplars Populus spp. and willows Salix spp. 22 cm and 33 cm DBH) selected for foraging by juveniles than non-used areas. These results suggest that foraging conditions may drive, at least partly, habitat use decisions by juvenile birds. We also discuss the potential influence of intraspecific competition, the search for a future breeding territory in the early postfledging period and predation avoidance on habitat use decisions by juvenile birds. Contrary to previous studies on migrant forest birds, postfledging juvenile woodpeckers selected the same habitat as for the breeding adults (i.e. old oak forest), indicating that migrant and resident specialist avian species may require different conservation actions. Conservation strategies of woodpecker populations should consider the protection of old oak forests with high densities of large trees to provide suitable habitat to breeding adults and postfledging juveniles. The habitat improvement for this indicator and umbrella species would also favour other organisms that depend on characteristics of old-growth oak forests.